Whole-Genome Sequencing of the Opportunistic Yeast Pathogen Candida inconspicua Uncovers Its Hybrid Origin - Mixão, Verónica; Hansen, Antonio Perez; Saus, Ester; Boekhout, Teun; Lass-Florl, Cornelia; Gabaldón, Toni (Frontiers in Genetics, 2019)
Fungal infections such as those caused by Candida species are increasingly common complications in immunocompromised patients. The list of causative agents of candidiasis is growing and comprises a set of emerging species whose relative global incidence is rare but recurrent. This is the case of Candida inconspicua, which prevalence has increased tenfold over the last years. To gain novel insights into the emergence of this opportunistic pathogen and its genetic diversity, we performed whole genome sequencing of the type strain (CBS180), and of ten other clinical isolates. Our results revealed high levels of genetic heterozygosity structured in non-homogeneous patterns which are indicative of a hybrid genome shaped by events of loss of heterozygosity. All analyzed strains were hybrids and could be clustered into two distinct clades. We found large variability across strains in terms of ploidy, patterns of loss of heterozygosity, and mitochondrial genome heterogeneity that suggest potential admixture between hybrids. Altogether, our results identify a new hybrid species with virulence potential towards humans and underscore the potential role of hybridization in the emergence of novel pathogenic lineages.